PERBANDINGAN PENGGUNAAN LEM POLYURETHANE DAN MORTAR TERHADAP VARIASI WAKTU IKAT TERHADAP KEKUATAN GESER PEREKAT PADA PEMASANGAN BETON RINGAN - Harprastanti, Primasiwi; Fikri Praharseno; Wasino; Supriyadi; Agung Rahmatyuda (Politeknik Negeri Semarang, 2025)
Lightweight concrete is an increasingly popular construction material because of its lightweight and high strength, so effective adhesive technology is needed to increase the adhesion between elements. This study aims to compare the effectiveness of the use of polyurethane glue with MU 380 on the variation of bonding time and shear strength of bonding in the installation of lightweight brick concrete. In this study, tests were conducted on lightweight brick concrete joints using two types of adhesives, namely polyurethane glue and mortar. The variation of bonding time applied to the application of polyurethane glue includes 5, 10, 15, 20, 25, 30, 60, 360, 720, and 1440 minutes. Meanwhile, for mortar adhesive, the bonding time used is 5, 10, 15, 20, 25, 30, 60, 360, 720, and 1440 minutes. After the application of glue and mortar, shear strength testing was carried out to determine how well the concrete joints can withstand shear loads. The results showed that polyurethane glue produced much higher shear strength than mortar at all bonding times tested. The highest average shear strength was obtained at a setting time of 25 minutes for polyurethane glue, which was 21.85 MPa, while the average maximum strength of the mortar occurred at a setting time of 360 minutes with a value of 3.123 MPa. In addition, the shorter setting time of polyurethane glue allows for better installation time efficiency.